2011
DOI: 10.1007/s00066-010-2203-5
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C – A Fast and Reliable Biomarker for Glomerular Filtration Rate in Head and Neck Cancer Patients

Abstract: Cystatin C-based GFR estimates showed the overall strongest correlation to the reference method. Thus, we recommend cystatin C for GFR estimation in HNC patients as an alternative method to the estimated creatinine clearance in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
2
16
2
2
Order By: Relevance
“…[25][26][27] However, in a study regarding head and neck cancers, cystatin C was noted as a proper parameter for GFR measurement. 17 No correlation was found between the advanced tumor grade and cystatin C level in our study. Studies with larger patient groups will be necessary to prove that the serum cystatin C level is a proper method in determining the cisplatininduced renal damage.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…[25][26][27] However, in a study regarding head and neck cancers, cystatin C was noted as a proper parameter for GFR measurement. 17 No correlation was found between the advanced tumor grade and cystatin C level in our study. Studies with larger patient groups will be necessary to prove that the serum cystatin C level is a proper method in determining the cisplatininduced renal damage.…”
Section: Discussioncontrasting
confidence: 68%
“…[12][13][14][15] Some studies have demonstrated that cystatin C was a better indicator in determining the renal function compared to creatinine in the patients receiving cisplatinbased chemotherapy. 8,[16][17][18] Furthermore, it was reported that cystatin C was found in higher concentrations in the tissues and body fluids of breast and prostate cancer patients and this was correlated with the aggressive form of the cancer. 19,20 The aim of our study was to evaluate the correlation of the serum cystatin C levels with the serum creatinine levels and GFR calculated by CockcroftGault and MDRD formulations in the patients who received cisplatin-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in accordance with the results of Salek et al [13]. This is likely because creatinine is not only filtrated through glomeruli, but is also secreted from the proximal tubuli, leading to overestimation [23]. eGFR scr is the current equation recommended for use in clinical practice [24].…”
Section: Discussionsupporting
confidence: 89%
“…It is expressed at a constant rate in all nucleated cells. Because cystatin C is cleared exclusively through the kidney, its concentration depends solely on the GFR and is unaffected by muscle mass, age, race, or gender (13) . Many investigations have shown that CysC is superior to sCr as a marker for AKI (5) .…”
Section: Introductionmentioning
confidence: 99%